Cyclosporine Treatment in Cats with Presumed Chronic Pancreatitis—A Retrospective Study - Nina Hoeyrup; Thomas Spillmann; Linda Toresson (Animals, 2021)
Chronic pancreatitis (CP) is a common disease in middle-aged to older cats. Cyclosporine has been suggested as an alternative treatment when other immunosuppressive treatments are insufficient or contraindicated. However, no published studies have investigated its efficacy on feline CP. The aim of this retrospective study was to evaluate the efficacy of cyclosporine on supranormal serum feline pancreas-specific lipase (Spec fPL) concentrations in cats with presumed CP. Inclusion criteria were history and clinical signs suggestive of CP, serum Spec fPL concentrations above 5.3 μg/L (reference range 0–3.5 μg/L, equivocal range 3.6–5.3 μg/L) on at least two occasions and treatment with cyclosporine for at least three weeks. Serum Spec fPL was analyzed at Idexx Laboratories, Kornwestheim, Germany. Nineteen cats, aged 6.9–17.5 years (median 11.6), were included. No pancreatic biopsies were available. Median (range) serum Spec fPL concentration was 14.2 μg/L (6.1–43.3) at baseline and 6.7 μg/L (0.9–23.6) at follow-up. Cyclosporine treatment (5.0–7.9 mg/kg orally SID) was associated with a significant reduction in serum Spec fPL concentrations (p < 0.001) at follow-up after 23–206 days (median 35). Body weight decreased significantly between inclusion and follow-up (p = 0.013). Significant improvement of clinical signs could not be measured (p = 0.781). This study has several limitations, including unstandardized treatment length and dose, no control group and lack of pancreatic biopsies. Despite the limitations, our results suggest that cyclosporine treatment reduces supranormal serum Spec fPL concentrations in cats with presumed CP.